Introducing a soil universal model method (SUMM) and its application for qualitative and quantitative determination of poly(ethylene), poly(styrene), poly(vinyl chloride) and poly(ethylene terephthalate) microplastics in a model soil. (June 2019) - David, Jan; Weissmannová, Helena Doležalová; Steinmetz, Zacharias; Kabelíková, Lucie; Demyan, Michael Scott; Šimečková, Jana; Tokarski, David; Siewert, Christian; Schaumann, Gabriele E.; Kučerík, Jiří
Abstract: Methods for analysis of microplastic in soils are still being developed. In this study, we evaluated the potential of a soil universal model method (SUMM) based on thermogravimetry (TGA) for the identification and quantification of microplastics in standard loamy sand. Blank and spiked soils (with amounts of one of four microplastic types) were analyzed by TGA. For each sample, thermal mass losses (TML) in 10 °C intervals were extracted and used for further analysis. To explain and demonstrate the principles of SUMM, two scenarios were discussed. The first refers to a rare situation in which an uncontaminated blank of investigated soil is available and TML of spiked and blank soils are subtracted. The results showed that the investigated microplastics degraded in characteristic temperature areas and differences between spiked and blank soils were proportional to the microplastics concentrations. The second scenario reflects the more common situation where the blank is not available and needs to be replaced by the previously developed interrelationships representing soil universal models. The models were consequently subtracted from measured TML. Sparse principal component analysis (sPCA) identified 8 of 14 modeled differences between measured TMLs and the universal model as meaningful for microplastics discrimination. Calibrating various microplastics concentrations with the first principal component extracted from sPCA resulted in linear fits and limits of detection in between environmentally relevant microplastics concentrations. Even if such an approach using calculated standards still has limitations, the SUMM shows a certain potential for a fast pre-screening method for analysis of microplastics in soils. Graphical abstract: Image 104354 Highlights: Relationships of soil components represent soil universal model indicators. Soil universal models can replace soil standards. Deviations from soil universal model indicators indicates soil contamination. Indicators are promising for qualitative and quantitative determination of studied μP (microplastics) except poly (ethylene).